Disharmoni Kebijakan Prioritas BUMN dalam UU Persaingan Usaha terhadap Prinsip Level Playing Field di Indonesia - Muhammad Baihaqy Ash Shiddiqi; Akhmad Farroh Hasan (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
The existence of Badan Usaha Milik Negara (BUMN) in the Indonesian economic system bears a constitutional mandate under Pasal 33 Undang-Undang Dasar 1945 to control production sectors vital to the state and crucial for the public livelihood. However, following the enforcement of Peraturan Menteri BUMN Nomor PER-2/MBU/3/2023 tentang Pedoman Tata Kelola dan Kegiatan Terpadu BUMN which intensifies the